The Urgency of Establishing Funding Regulations for Refugees by Faith-Based Organizations in Indonesia - Fitria; Susetyo, Heru; Rahmawati, Nurlaili; Hanah, Ummu (Brawijaya Law Journal, 2025)
More than 12,000 refugees in Indonesia face a life of uncertainty, as the country is not considered a destination for them. Moreover, Indonesia needs more adequate regulations regarding refugees. In practice, handling refugee issues in Indonesia relies on the United Nations High Commissioner for Refugees (UNHCR) and the International Organization for Migration (IOM). Unfortunately, most refugees cannot return to their home countries, primarily due to ongoing conflicts, with only about 1–1.5% being resettled in third countries. Consequently, they remain in Indonesia for years, even decades, without clear prospects for their future. This paper analyzes the urgency of establishing funding for refugees by civil society, mainly through faith-based organizations (FBOs), viewed through Jacques Derrida's theory. In this research, a socio-legal method was employed, which examines law through the lens of social phenomena. The research team's key findings are as follows: first, the interviewed refugees, having undergone several migrations, find themselves "stranded" in Indonesia. Although they feel safe, they lament the lack of a dignified life. Second, the significant role of FBOs is highlighted when the UNHCR and IOM cannot handle refugee issues optimally (Ashutosh & Mountz, 2011). Third, these facts raise the need for regulations concerning donations by civil society, especially FBOs for refugees, to ensure more humane treatment. This aligns with Derrida's perspective on hospitality, which seeks a balance between the extremes of neglect and boundless kindness (unconditional hospitality) towards the presence of foreigners in a country, in this case, refugees in Indonesia.